“The Role of Institutional Innovation Council in Enhancing Innovation and Entrepreneurship in Higher Education” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Institutional Innovation Councils (IICs), initiated under the aegis of the Ministry of Education, Government of India, have emerged as a significant mechanism for fostering a culture of innovation and entrepreneurship in higher education institutions. The primary objective of IICs is to systematically nurture innovative thinking, problem-solving abilities, and entrepreneurial skills among students and faculty members. This study examines the role of Institutional Innovation Councils in enhancing innovation and entrepreneurship within higher education institutions by promoting start-up ecosystems, industry–academia collaboration, capacity-building programs, and experiential learning opportunities. Using a structured research framework, the study analyzes the effectiveness of IIC initiatives such as innovation challenges, entrepreneurship development programs, incubation support, and intellectual property awareness. The findings highlight that IICs play a pivotal role in strengthening innovation culture, improving entrepreneurial intent among students, and aligning academic institutions with national innovation goals. The study concludes that effective implementation of IIC activities significantly contributes to institutional transformation, skill development, and sustainable entrepreneurial outcomes in higher education.